Frequency of hypophosphatemia in critically ill children: risk factors and outcome - Saman, Uroosa; Noreen, Asma; Jamil, Mohammad T.; Khalid, Muhammad; Haq, Sidra; Haque, Anwarul (International Journal of Contemporary Pediatrics, 2022)
Background: Phosphorus plays a vital role in maintaining metabolism and energy of body. The objective of this study was to determine the frequency, risk factors and outcome of hypophosphatemia (HP) in critically ill children admitted in pediatric intensive care unit. Methods: This retrospective study included all critically-ill children having phosphate levels within 24 hours of admission from July 2019 to December 2020. Demographic, clinical and laboratory variables were collected. HP is defined as serum phosphorus level ≤4 mg/dl in this study. Descriptive statistics along with logistic regression analysis have been reported. Results: Prevalence of HP was 53.7% (94/175). Median age was 2 year (0.5-15) and male were 58.5% (106). Serum magnesium level [2.2 (1.5-12.1) vs. 1.8 (1.2-4.0) mg/dl] and serum calcium level [8.7 (.18-10.7) 8.0 (1.8-14.0) mg/dl] were significantly low in the HP group as compared to the normo-phosphatemic group. There was no significant association of hypo-phosphataemia with admitting diagnosis, ICU therapies, and medications on univariate analysis. Hypo-phosphataemia at admission had no effect on mortality. On multivariate analysis, only male gender demonstrated independent association with HP (OR: 2.2; 95% CI 1.2-4.1; p<0.01). Conclusions: HP is common in critically ill children and is significantly associated with male gender. Prospective, larger sample size studies are needed to study the prevalence and risk factors of HP at pediatric intensive care units.